Menelusuri Keterbatasan dan Heterogenitas Akurasi Nighttime Light sebagai Proksi Aktivitas Ekonomi di Tingkat Kabupaten/Kota - Lestari, Sintya Dwi; Pannu, Abdullah (Seminar Nasional Official Statistics, 2025)
The use of NTL data as a proxy for economic activity has gained attention in regional economic studies. However, its effectiveness varies across regions depending on sectoral composition and geographic characteristics. This study aims to evaluate the effectiveness of NTL as a proxy for economic activity at the regency/city level in South Sulawesi Province during the 2014–2024 period. Using a fixed effects panel regression model, the results indicate a positive and significant relationship between NTL and GRDP at constant prices, with NTL explaining a substantial portion of interregional economic variation. However, RMSE-based accuracy analysis reveals spatial heterogeneity, with areas such as Makassar and Soppeng showing high prediction errors, indicating the limited ability of NTL to capture local economic dynamics. Additional control variables and remote sensing indicators failed to improve model performance. Thus, while NTL holds promise as an alternative economic indicator, its applicability must be contextually adapted to regional characteristics.